ANALYSIS OF PT. ARJUNA YOGA SAKTI PERFORMANCE BASED ON BALANCED SCORECARD METHOD - Ni Made Dharma Shantini Suena; Achmad Fudholi; Satibi Satibi (Faculty of Pharmacy, Universitas Gadjah Mada)
Balanced Scorecard (BSC) is a comprehensive and coherent framework to translate the vision and mission of a company into a unified set of performance measures. PT. Arjuna Yoga Sakti is one company which produces cosmetics in the form of pharmaceutical preparations of herbal ingredients. The aim of this research is to identify the performance of PT. Arjuna Yoga Sakti through the BSC performance measurement, using the four perspectives namely financial, customer, internal business processes, as well as the learning and growth. This research is a descriptive research according to the level of explanation of its qualitative and quantitative data. Ten indicators are measured based on the four perspectives of BSC, which are the research variables. Eight indicators examined through in-depth interviews with stakeholders in this case the company owner. Two other indicators, i.e. customer satisfaction and employee satisfaction, examined using a questionnaire with research subjects were 100 customers that are sampled by purposive sampling, and using all employees of the company (saturated sampling). The questionnaire previously tested its validity and reliability using item analysis and Cronbach Alpha in SPSS for Windows version 12th. The result of performance measurement of PT. Arjuna Yoga Sakti using the four BSC perspectives is pretty good. Productivity per employee per month which is pretty high (8.84 million/month) and job satisfaction of employees is pretty good (Likert scoring 3.61) supports the production of cosmetic products both in sufficient time to be able to satisfy the customer (Likert scoring 4.15) and also encourage the growing number of customers (customer growth 20%). This gives a pretty good profit (ROI 36%, ROE 45%; Total Assets Turnover rate 1.4 times) for the company to continue to improve its performance is supported by adequate information systems. Key word: PT. Arjuna Yoga Sakti, the company’s performance, Balanced Scorecard